What makes a city breastfeeding friendly? A qualitative analysis of interviews with breastfeeding women from Europe and Asia - May Loong Tan; Elizabeth J. O’Sullivan; Jacqueline J. Ho; Amal Omer-Salim; Fionnuala M. McAuliffe (PLoS ONE, 2025)
Background The warm chain of support is the continuous enabling environment from the mother’s first contact with healthcare professionals during early pregnancy, birth and immediate post-partum period, her transition from healthcare facility to home, through to work and the community at large. A breastfeeding-friendly city should be able to support a breastfeeding journey across the warm chain. Objective To determine breastfeeding women’s perspective of an ideal breastfeeding-friendly city. Methods Between September 2021 and January 2022, twenty-two women who were breastfeeding or had ever breastfed in the last 5 years from Ireland and Malaysia were interviewed. A set of selection criteria was applied to ensure representation of a range of the characteristics known to be associated with breastfeeding success: diverse age groups, birth and breastfeeding experiences, culture and socioeconomical background. One-on-one semi-structured online interviews were conducted by the first author. Data were analysed using Braun and Clarke’s Thematic Analysis framework. Results One overarching theme of breastfeeding at the front and centre of the city, and three major themes were developed: 1. mothers feel supported when breastfeeding is prioritised; 2. when breastfeeding is visible in the environment, it becomes normalized; 3. there is a need to have seamless breastfeeding support across the continuum of the warm chain, and at all levels of society. Conclusions The findings demonstrated the importance of prioritized, and continuous support throughout the breastfeeding journey. The hopes and aspirations of a breastfeeding-friendly city expressed here would be useful for cities to consider when developing or implementing breastfeeding support programmes as well as guide development of indicators of a breastfeeding-friendly city.